2023
DOI: 10.1039/d3fo02271d
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei ET-22 and derived postbiotics reduce halitosis and modulate oral microbiome dysregulation – a randomized, double-blind placebo-controlled clinical trial

Abstract: Oral microbial dysbiosis is the primary etiologic factor for halitosis, which may be the critical preventive target for halitosis. This study included randomized controlled trials (RCT) assessing the effects of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…A positive reduction in breath VSC levels was observed in both ET‐22.L and ET‐22.HK groups after a 4‐week intervention, with a more significant decrease in the ET‐22.L group. Additionally, both ET‐22.L and ET‐22.HK altered the taxonomic composition of the salivary microbiome (Wuri et al., 2023). However, VSCs are not necessarily harmful and contribute significantly to the flavors of foods consumed by the human population.…”
Section: The Role Of the Oral Microbiota In Aroma Release And Perceptionmentioning
confidence: 99%
“…A positive reduction in breath VSC levels was observed in both ET‐22.L and ET‐22.HK groups after a 4‐week intervention, with a more significant decrease in the ET‐22.L group. Additionally, both ET‐22.L and ET‐22.HK altered the taxonomic composition of the salivary microbiome (Wuri et al., 2023). However, VSCs are not necessarily harmful and contribute significantly to the flavors of foods consumed by the human population.…”
Section: The Role Of the Oral Microbiota In Aroma Release And Perceptionmentioning
confidence: 99%
“…Our previous studies have reported that Lacticaseibacillus paracasei ET-22 (ET-22) [13,14] and Bifidobacterium lactis BL-99 (BL-99) [15] exhibited the benefit effects of modulating microflora, inhibiting pathogenic biofilm and relieving inflammation. The objective of the present study was to investigate the impact of thermal treatment on antioxidant, anti-inflammatory activities of ET-22 and BL-99 postbiotics.…”
Section: Introductionmentioning
confidence: 99%